Provider’s attitudes towards telehealth and parenting interventions during COVID-19 pandemic: an exploratory cross-sectional study from Brazil and Mexico - Marina Kohlsdorf; Cole Hooley; Alejandro L. Vázquez; Mariana M. Juras; Grant Decker; Taylor Iskalis; Kayla Miller; Quinn Tompkins; Nancy G. A. Buenabad; Michela Ribeiro; Acileide C. F. Coelho; Ana A. Baumann (Psicologia: Reflexão e Crítica)
Abstract Background The COVID-19 pandemic presented challenges for mental health providers all over the world, since they had to abruptly change from in person assistance to remote meetings. The adverse effects from social isolation were critical in Latinx populations such as Brazil and Mexico, since these countries faced a great amount of social, health, and economic burden during the pandemic, which affected families' access to care and increased inappropriate parenting practices. Objective This study aimed to understand the impacts of adapting parenting interventions to online sessions for Brazilian and Mexican providers, due to the COVID-19 pandemic. Methods Sixty-two Brazilian and 49 Mexican mental health care providers that worked with parenting interventions (including psychologists, social workers, occupational therapists, counselors, and others) took part in this study. The measures included two standardized questionnaires (the Questionnaire about Acceptability, Feasibility and Appropriateness of Telehealth, and the Epidemic-Pandemic Impact Inventory), demographic data, and complementary items developed specially for this study. All measures were translated from English to Brazilian Portuguese and Spanish, resulting in five sets of themes related to (a) service delivery, (b) barriers to mental health assistance, (c) acceptability, feasibility and appropriateness of telehealth, and (d) impacts of pandemic on providers´ professional and personal lives. Results For all participants, adapting to online sessions presented challenges related to technology issues, time management, less healthy habits, and overload of chores between work and home tasks, besides concerns related to confidentiality and privacy. Kruskal–Wallis Rank Sum Tests revealed that Mexican providers reported less barriers regarding technology, while Brazilian providers mentioned less economic impact. Conclusion This study describes a comparison between providers of two Latinx countries facing demands from COVID19 pandemic, showing common challenges and specific barriers. Suggestions are presented in order to improve the experience of telehealth (i.e., tailored sessions, guidelines for families that ensure privacy, and policies that can increase telehealth access for vulnerable populations).